Perioperative Complications Following Surgery for Necrotizing Enterocolitis - Mutanen, Annika; Pierro, Agostino; Zani, Augusto (European Journal of Pediatric Surgery, 2018)
Necrotizing enterocolitis (NEC) is a devastating condition that mainly affects premature infants. Advanced cases of NEC require surgical treatment, which in up to 70% of infants is associated with significant perioperative morbidity including anastomosis- or enterostomy-related complications, sepsis, peritonitis, and wound infections. Moreover, the perioperative complications may compromise the long-term gastrointestinal and neurodevelopmental outcome of patients requiring surgery for NEC.
Keywords: infant; sepsis; surgical site infection; intestinal failure; short gut